Calibration and assessment of reliability-based serviceability limit state procedures for foundation engineering. Issue 4 (1st October 2016) - Huffman, Jonathan C.; Martin, John P.; Stuedlein, Armin W.
ABSTRACT: This paper uses an existing reliability-based serviceability limit state (RBSLS) procedure to illustrate some of the critical elements in the calibration of RBSLS models and to serve as guide for future calibration work. The impact of copula model selection and therefore correlation structure of bearing pressure-displacement model parameters on reliability is assessed. Then, a framework for evaluating bearing pressure-displacement normalisation techniques is presented as a revision to the existing RBSLS procedure proposed. The reliability of the revised RBSLS procedure is then evaluated by comparing its accuracy to newly conducted, full-scale loading tests of spread footings on aggregate pier-reinforced ground. It is shown that the new RBSLS procedure produces a more accurate estimate of the actual reliability and validates the proposed framework.